2017
DOI: 10.1002/jcph.842
|View full text |Cite
|
Sign up to set email alerts
|

A Novel NF‐κB Inhibitor, Edasalonexent (CAT‐1004), in Development as a Disease‐Modifying Treatment for Patients With Duchenne Muscular Dystrophy: Phase 1 Safety, Pharmacokinetics, and Pharmacodynamics in Adult Subjects

Abstract: In Duchenne muscular dystrophy (DMD), NF‐κB is activated in skeletal muscle from infancy regardless of the underlying dystrophin mutation and drives inflammation and muscle degeneration while inhibiting muscle regeneration. Edasalonexent (CAT‐1004) is a bifunctional orally administered small molecule that covalently links 2 compounds known to inhibit NF‐κB, salicylic acid and docosahexaenoic acid (DHA). Edasalonexent is designed to inhibit activated NF‐κB upon intracellular cleavage to these bioactive componen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 50 publications
(100 reference statements)
5
39
0
Order By: Relevance
“…Our data further provide a novel understanding of E 2induced apoptosis through extensive interactions of ERa with inflammation-and stress-associated transcription factors, such as NF-kB and PPARg (15,16,27), which facilitates apoptosisassociated inflammation and stress after long-term E 2 deficiency. Importantly, these transcription factors are also therapeutic targets for different diseases (51)(52)(53). Together, this study not only supports the deployment of antiglucocorticoids to enhance sex steroid-induced apoptosis in cancer therapy, but also provides an insight into the mechanism of MPA with glucocorticoid activity to increase breast cancer incidence in the WHI.…”
Section: Discussionsupporting
confidence: 62%
“…Our data further provide a novel understanding of E 2induced apoptosis through extensive interactions of ERa with inflammation-and stress-associated transcription factors, such as NF-kB and PPARg (15,16,27), which facilitates apoptosisassociated inflammation and stress after long-term E 2 deficiency. Importantly, these transcription factors are also therapeutic targets for different diseases (51)(52)(53). Together, this study not only supports the deployment of antiglucocorticoids to enhance sex steroid-induced apoptosis in cancer therapy, but also provides an insight into the mechanism of MPA with glucocorticoid activity to increase breast cancer incidence in the WHI.…”
Section: Discussionsupporting
confidence: 62%
“…The 24-hour plasma exposures at this dosage were 450 and 270 ng hr/ml for edasalonexent and CAT-1041, respectively. These values are at the lower end of clinical exposures observed in phase 1 studies in adults and boys with DMD (30), suggesting that efficacy is obtained in the mdx mouse at clinically relevant exposures. Moreover, the exposure of edasalonexent was 7.2-fold greater in the gastrocnemius muscle compared with plasma and 4.0-fold higher in muscle than plasma for CAT-1041, demonstrating that both molecules are able to effectively reach and accumulate in skeletal muscle.…”
Section: Methodsmentioning
confidence: 84%
“…An attractive feature of the compounds used in the current study is that they are orally bioavailable small molecules with low risk of toxicity that exhibit substantial NF-κB inhibitory effects and demonstrate the capacity to improve the dystrophic muscle phenotype in 2 animal models, with no signs of adverse events. In fact, a recently completed phase 1 trial with edasalonexent demonstrated high safety profiles in subjects after 2 weeks of administration (30), with plasma exposure levels that exceeded those observed in mice.…”
Section: Discussionmentioning
confidence: 99%
“…17,18 Regulatory T cells have been shown to block and/or ameliorate dystrophic symptoms in mouse and canine DMD models. 7,17,[19][20][21][22][23][24][25][26] The nuclear pore functions as a key regulator of intracellular molecules such as proteins, RNA molecules, and ions. 27,28 The nuclear pore consists of various regulatory proteins called nucleoporins that together form the nuclear pore complex (NPC).…”
Section: Introductionmentioning
confidence: 99%